Tetracaine stimulates insulin secretion through the mobilization of Ca2+ from thapsigargin- and IP3-insensitive Ca2+ reservoir in pancreatic β-cells - Bosqueiro, José Roberto [UNESP]; Carneiro, Everardo Magalhães; Bordin, Silvana; Boschero, Antonio Carlos (Canadian Science Publishing, 2000)
The effect of tetracaine on 45Ca efflux, cytoplasmic Ca2+ concentration [Ca2+](i), and insulin secretion in isolated pancreatic islets and β-cells was studied. In the absence of external Ca2+, tetracaine (0.1-2.0 mM) increased the 45Ca efflux from isolated islets in a dose-dependant manner. Tetracaine did not affect the increase in 45Ca efflux caused by 50 mM K+ or by the association of carbachol (0.2 mM) and 50 mM K+. Tetracaine permanently increased the [Ca2+](i) in isolated β-cells in Ca2+-free medium enriched with 2.8 mM glucose and 25 μM D-600 (methoxiverapamil). This effect was also observed in the presence of 10 mM caffeine or 1 μM thapsigargin. In the presence of 16.7 mM glucose, tetracaine transiently increased the insulin secretion from islets perfused in the absence and presence of external Ca2+. These data indicate that tetracaine mobilises Ca2+ from a thapsigargin-insensitive store and stimulates insulin secretion in the absence of extracellular Ca2+. The increase in 45Ca efflux caused by high concentrations of K+ and by carbachol indicates that tetracaine did not interfere with a cation or inositol triphosphate sensitive Ca2+ pool in β-cells.
Keywords: Ca2+; Insulin secretion; Tetracaine; β-cells